TOXIC EFFECTS OF HYDROXYCHLOROQUINE ON THE CHOROID: Evidence From Multimodal Imaging. Issue 5 (May 2019) - Ahn, Seong Joon; Ryu, So Jung; Lim, Han Woong; Lee, Byung Ro
Abstract : Purpose: To investigate the choroidal changes that occur in hydroxychloroquine (HCQ) retinopathy using multimodal imaging including fluorescein angiography, indocyanine green angiography, and optical coherence tomography (OCT) angiography and to correlate these changes with retinal findings obtained using OCT and fundus autofluorescence. Methods: In 20 patients (n = 40 eyes) with systemic lupus erythematosus or rheumatoid arthritis diagnosed to have HCQ retinopathy, imaging modalities including swept-source OCT, fundus autofluorescence, fluorescein angiography, indocyanine green angiography, and OCT angiography were used to evaluate retinal and choroidal changes associated with retinopathy. The assessments included specific findings such as presence of hyperfluorescent or hypofluorescent lesions on angiography and signal void zones on OCT angiography, their frequencies, and the correlations among the retinal and choroidal findings. These findings were also correlated with the severity of retinopathy. Retinopathy progression was defined using fundus autofluorescence and OCT and correlated with the retinal/choroidal findings. Results: Fluorescein angiography demonstrated a hyperfluorescent area, which reflects a defective retinal pigment epithelium, with multiple tiny dark spots within the area. Indocyanine green angiography showed a hypofluorescent area with dark spots, which was matched to the hypoautofluorescent area on fundus autofluorescence. Although there were no specific morphologic abnormalities in the choroid layers using en face choroidal imaging, OCT angiography demonstrated signal void areas on the choriocapillaris in the areas of the retinal pigment epithelium defect. Even after cessation of HCQ, there was progression of retinopathy in eyes with choroidal involvement, particularly on the area of choroidal findings. Conclusion: Multimodal imaging demonstrates choriocapillaris degeneration in eyes with HCQ retinopathy, particularly those with severe retinopathy. The choroidal change was associated with outer retinal toxicity of HCQ. Abstract : Supplemental Digital Content is Available in the Text.Patients with hydroxychloroquine retinopathy showed choriocapillaris degeneration and thinning, particularly in those with severe retinopathy, suggesting the choroidal toxicity of hydroxychloroquine. The changes were associated with retinopathy progression after drug cessation.